Blood donation during COVID-19 lockdown and its association with anger and stress: A cross-sectional study from Syria - Kakaje, Ameer; Mansour, Sabina; Ghareeb, Ayham; Hosam Aldeen, Osama (Frontiers in Sociology, 2023)
Background Syria has suffered for nine years of war and there were huge demands for blood during and after the lockdown from Coronavirus disease of 2019 (COVID-19). This study aims to assess blood donation practices in Syria and their association with multiple factors. Methods Online questionnaires were distributed to Social Media groups. They included stress, anger, and COVID-19 distress questions. Results This study included 1423 participants, 899 (63.2%) of which were females. Only 48.5% have donated blood, of which 33.3% donated only once in their lifetime. Not having a good reason to donate blood was the main declared reason for not donating. Among people who donated bloods, obtaining a document was the main reason for donating in (64.8%). Stress, anger, and having fears from getting infected did not have a crucial effect on blood donation, and its patterns. Losing someone close and being endangered from war were associated with more frequent blood donation in contrast to being distressed from war. Conclusion Distress from COVID-19, stress and anger were not the main reason for the decrease in blood donation. Spreading the culture of volunteer blood donating is crucial to combat the shortage during catastrophes.